Immediate dam-sourced colostrum provision reduces calf mortality - management practices and calf mortality in large dairy herds - Steffi Keller; Karsten Donat; Stefanie Söllner-Donat; Axel Wehrend; Anne Klassen (Acta Veterinaria Scandinavica)
Abstract Background Farm-specific management practices greatly impact calf mortality rates. This cross-sectional study aimed to analyse the association between calf mortality and management practices in large dairy farms. A total of 93 dairy farms were voluntarily included in the study. All farms reared their own youngstock, and all but one kept more than 100 dairy cows. From March 2017 to March 2018, calf management practices were monitored during a farm visit, and farm managers were surveyed regarding calving procedures, neonate management, and environmental factors. Data were collated and analysed in conjunction with the 2017 calf mortality rate, as determined for each farm by using data from the German database of animal origin and movement (HI-Tier). All variables from the topics of colostrum supply, calf feeding, housing, health related information and calving preparation of the cows that resulted in P ≤ 0.1 in the analysis of variance were assumed to be associated with the calf mortality rate and were considered for a general linear mixed regression model. Results According to the data from the HI-Tier database of the 93 study herds from 2017, 54,474 calves were born alive and 3,790 calves died within the first six months of life. The calf mortality rate was lower on farms where calves were immediately provided with dam-sourced colostrum. Farm managers perceiving dust as the primary factor precipitating respiratory disease on the farm was positively associated with calf mortality. Regularly replacing bucket teats correlated with lower calf mortality rates compared to replacing them only upon detection of abrasion. Conclusions The study findings suggest that feeding calves with dam-sourced colostrum can potentially reduce overall calf mortality within the herd. This management practice holds comparable importance to ensuring successful passive transfer through timely and adequate colostrum feeding. Moreover, maintaining a low dust environment for the calves and consistently replacing bucket teats play significant roles in promoting better overall calf health.